PENGARUH PENGALAMAN DAN KEMAMPUAN BERPIKIR KREATIF TERHADAP KREATIVITAS MAHASISWA FAKULTAS EKONOMI UNIVERSITAS HKBP NOMMENSEN - ANNE RUMONDANG MALAU; YOHANA EPIPANIAS HUTABARAT (LP2MTBM MAKARIOZ, 2018)
This research tests and analyzes the influence of experience and creative thinking skills on student creativity. The researchwas conducted on 120 students who were studying at the faculty of Economics of HKBP Nommensen University. Samplingis done with the technique purposive (intentionally). Data collection using online questionnaires to get information about theexperience, creative thinking skills and creativity of students. Based on the research results shows the experience andcreative thinking ability to positively influence the student's creativity. The results of the hypothesis testing showed that theexperience of significant positive effect on student creativity and creative thinking ability has a significant positive effect onstudent creativity. The hypothesis testing uses Structural Equation Modelling (SEM) with the help of the LISREL program.